Paper inventions : machines that move, drawings that light up, and wearables and structures you can cut, fold, and roll - Ceceri, Kathy, ....- (San Francisco : Maker Media, 2015)
Paper is incredible stuff. It's easy to cut, but incredibly strong. It's disposable, but can last for centuries. It can stand as stiff as a board, pop up like a spring, or float like a leaf. And its invention changed the world forever. Perfect for kids, parents, and educators, Paper Inventions is a project-based book with full color illustrations, step-by-step instructions, supply lists, and templates that allow you to follow along with the book or devise something entirely new. Each chapter features new projects that will challenge and intrigue everyone, from beginning to experienced Makers.
Keywords: Paper work; Handicraft